Understanding Police Discretion in Zimbabwe: Institutional Drivers and Consequences for Community Relations in Harare Metropolitan Province - Joshua Foma; Riska Sri Handayani; Husnul Fitri (International Journal Labs, 2025)
Police discretion is central to community policing, influencing how law enforcement officers interpret and apply the law in everyday interactions. In Harare Metropolitan Province, police discretion is particularly visible in informal market areas and at urban roadblocks, where enforcement practices often appear inconsistent. Although statutory frameworks guide police authority, a gap remains between legal expectations and the practical application of discretion, contributing to community mistrust and weakened police legitimacy. This research examines: (1) the nature of discretionary policing in Harare, (2) the institutional and socio-political factors influencing discretionary decision-making, and (3) the effects of discretionary practices on police–community relations. Understanding these dynamics is important for strengthening democratic policing and promoting public trust. A qualitative research design was adopted, utilizing secondary data from academic literature, legal documents, policy reports, and recent empirical studies relevant to policing in Zimbabwe. Findings show that police discretion is shaped by resource limitations, weak oversight mechanisms, and socio-political influences. In areas such as Mbare Musika, Machipisa, and major commuter routes within Harare Metropolitan Province, police discretionary decisions frequently lack consistency and transparency, leading to perceptions of selective law enforcement and diminished community cooperation. Discretionary policing practices have significant implications for public trust and the effectiveness of community policing. Strengthening accountability systems, improving law enforcement officers' training, and enhancing collaborative police–community engagement are recommended to restore legitimacy and support safer community environments.